“Excavate” The Impact of Word of Mouth Towards the Intention to Purchase Mobile Phone Among Older Consumers - Arman Hj. Ahmad; Izian Idris; Siti Suhana Alias; Ching Yen Wern; Adibah Zainualdin; Rafiatul Adlin Hj. Mohd. Ruslan; Diananda Fitri Pitari (International Journal of Business and Quality Research, 2025)
Mobile phones in modern times are a ‘must have’ item in keeping up with the latest happenings. Internal and external influences can however impact consumers’ intention to purchase a mobile phone. This paper aims to investigate the impact of word of mouth (WOM) towards older consumers’ purchase intention for mobile phones. Literature indicated that older consumers are vulnerable to this sort of influence especially when they deemed the content of advertising messages originated from a credible source. Furthermore, emotional appeal messages are influential in the behavioural purchase intention of the older population compared to the younger population due to the limited time perceived by older consumers and their decreased cognitive abilities. Primary data in this study is collected by a self-administered questionnaire involving 180 respondents selected through the simple random sampling approach. The sample population was all pre-determined to be aged above 50 years old. Analyses of data collection were done using SPSS to test the proposed hypotheses. Findings from this study aid marketer with their marketing campaigns for mobile phones with an enhanced understanding of the older consumer segment which possesses higher disposable income and purchasing power.